2021
DOI: 10.1186/s12886-021-02179-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ocular damage after recovery from COVID-19: lack of evidence at three months

Abstract: Importance A small number of COVID-19 patients has been reported to suffer from acute keratoconjunctivitis. In very rare cases, acute inflammatory retinal vein occlusion, papillophlebitis or retinopathy have been observed. Objective To determine possible long-term effects on the eye, especially on the retina, in patients who had suffered from COVID-19 at least 3 months after recovery. Design Prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, ocular impairments in COVID patients (often due to retinal manifestations in vein occlusions) were reported, potentially leading to visual impairment 50 57 . Brantl et al 58 found no significant changes in the visual functions after three months. However, they also state that the database is insufficient to be certain.…”
Section: Related Workmentioning
confidence: 94%
“…For example, ocular impairments in COVID patients (often due to retinal manifestations in vein occlusions) were reported, potentially leading to visual impairment 50 57 . Brantl et al 58 found no significant changes in the visual functions after three months. However, they also state that the database is insufficient to be certain.…”
Section: Related Workmentioning
confidence: 94%
“…It is vital to highlight Brantl’s [ 43 ] study, which did not find any retinal signs in patients 3 months post COVID-19 recovery. Twenty-one patients were examined 3 months after their initial presentation to the emergency department (14 had been hospitalised and 7 discharged home).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cardiovascular disease, an increased likelihood of ESRD (~2‐fold [UKB] and 1.2‐fold [HK]) was observed following COVID‐19 in people with diabetes, indicating that the long‐term management postdiagnosis with COVID‐19 in such patients should not only focus on cardiovascular, but also on microvascular, disease. Previously, some studies also reported risks associated with long COVID for decline in kidney function (nephropathy) leading to ESRD 40 and long‐term ocular damage in COVID‐19 survivors, leading to diabetic retinopathy 41 . Although statistically significant risks were associated with a few microvascular complications in this study, like retinopathy (HR [UKB]: 1 [95% CI: 1.2, 2.2]) and nephropathy (HR [HK]: 1.2 [95% CI: 1.1, 1.3]), others did not always reach statistical significance, possibly because of the small sample size of patients developing these complications.…”
Section: Discussionmentioning
confidence: 99%